2013
DOI: 10.3727/215517913x666468
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and Stability of Neural Differentiation of Androgenetic Murine ES Cell-Derived Neural Progenitor Cells

Abstract: Uniparental zygotes with two paternal (androgenetic, AG) or two maternal genomes (gynogenetic, GG) cannot develop into viable offsprings but form blastocysts from which pluripotent embryonic stem (ES) cells can be derived. For most organs, it is unclear whether uniparental ES cells can give rise to stably expandable somatic stem cells that can repair injured tissues. Even if previous reports indicated that the capacity of AG ES cells to differentiate in vitro into pan-neural progenitor cells (pNPCs) and into c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
9
0
1
Order By: Relevance
“…In differenzierenden AG-ES-Zellen zeigte sich, dass diese Zellen trotz eines fehlenden mütterlichen Genoms neurale Stammzellen (AG-NSCs) bilden, die sich in ihrer Fähigkeit zur Selbsterneuerung und im Multilinien-Differenzierungspotenzial nicht von normalen neuralen Stammzellen (NSCs) unterscheiden (Dinger et al, 2008). Ferner können AG-ES-Zellen zu dopaminergen Neuronen 25 differenzieren (Choi et al, 2005), die neuronale Aktionspotenziale generieren (Wolber, 2013). Dabei bleibt die rein väterliche Genexpression erhalten (Dinger et al, 2008).…”
Section: Mesenchymale Stamm-/stromazellen (Mscs)unclassified
“…In differenzierenden AG-ES-Zellen zeigte sich, dass diese Zellen trotz eines fehlenden mütterlichen Genoms neurale Stammzellen (AG-NSCs) bilden, die sich in ihrer Fähigkeit zur Selbsterneuerung und im Multilinien-Differenzierungspotenzial nicht von normalen neuralen Stammzellen (NSCs) unterscheiden (Dinger et al, 2008). Ferner können AG-ES-Zellen zu dopaminergen Neuronen 25 differenzieren (Choi et al, 2005), die neuronale Aktionspotenziale generieren (Wolber, 2013). Dabei bleibt die rein väterliche Genexpression erhalten (Dinger et al, 2008).…”
Section: Mesenchymale Stamm-/stromazellen (Mscs)unclassified
“…Those RPE cells survived in a host eye and rescued retinal function after subretinal transplantation in a rat model of retinal degeneration. However, a clinical study using pluripotent stem cell-derived RPE cells suggested a severe risk to patients, such as teratoma formation of the remaining undifferentiated ES cells in the host after transplantation [22]. In studies to improve the safety of cell replacement therapy, such as sorting of undifferentiated cells by using SOX1 or SSEA-5 and long-term culturing for differentiation [2122], somatic stem cells have emerged as a useful source for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ES cell-derived neural progenitor cells could give rise to teratomas in a host because of their unlimited self-renewal ability, while somatic stem cells cannot because of their limited self-renewal ability [30]. However, it is important to note that ES cells can proliferate in vitro and in vivo following transplantation.…”
Section: Introductionmentioning
confidence: 99%